Frozen-Thawed Sperm Analysis of Benign Prostatic Hyperplasia Dogs Treated With Finasteride - Flores, Renato Bueno; Angrimani, Daniel de Souza Ramos; Brito, Maira Morales; Almeida, Leticia Lima de; Lopes, João Vitor Menezes; Losano, João Diego de Agostini; Vannucchi, Camila Infantosi (Frontiers in Veterinary Science, 2022)
Benign Prostatic Hyperplasia (BPH) is a pathological condition that directly interferes with the reproductive potential of senile dogs, by leading to prostate enlargement and sperm injury, which in turn may compromise sperm freezeability. Moreover, albeit finasteride treatment reduces prostatic volume and blood supply and maintains seminal quality and testicular integrity, the effects of sperm samples submitted to cryopreservation after the finasteride treatment are still unknown. Thus, the aim of this study was to evaluate frozen-thawed semen of BPH dogs, as well as dogs subjected to BPH pharmacological treatment with finasteride. For such purpose, 20 dogs were previously selected and assigned to 3 experimental groups, according to BPH diagnosis and treatment with finasteride: Control (n=9), BPH Group (n=5) and BPH-Finasteride Group (n=6). Semen was subjected to one-step cryopreservation protocol with tris-fructose-citric acid extender with 5% glycerol and thawed at 37ºC for 30 seconds. Fresh and post-thaw sperm samples were evaluated for macroscopic parameters, sperm concentration, sperm motility kinetics, sperm mitochondrial activity and potential, oxidative stress, plasmatic and acrosome membrane integrity, sperm DNA fragmentation and sperm binding test on perivitelic membrane of chicken egg yolk. Regarding fresh semen, BPH-Finasteride group had the lowest ejaculate visual aspect (opacity), higher frequency of sperm flagellar beating (BCF) and percentage of sperm with medium velocity. Control group had the highest percentage of sperm DNA integrity compared to BPH group. For the frozen-thawed semen, Control group presented the highest percentage of spermatozoa with high mitochondrial activity. However, the BPH-Finasteride group showed higher number of sperm bound to the perivitelline membrane of chicken egg yolk compared to the BPH Group. Conversely, BPH group had higher percentage of DNA damage. In conclusion, the ejaculate of BPH dogs has higher susceptibility to cryoinjury, whereas finasteride-treated dogs have increased spermatozoa functional performance, suggesting a promising use of BPH dogs as semen donors in sperm cryopreservation programs.